Performance of tungro disease resistant rice lines in Lanrang, South Sulawesi, Indonesia - Mansur Mansur; Arif Muazam (Universitas Lampung, 2022)
Efforts to increase rice production and productivity nationally are still being disturbed by plant pest organisms. One of the diseases that have received serious attention is the tungro disease, which has the ability to attack rice plants in endemic areas. The purpose of this study was to investigate the resistance of several rice lines towards the Lanrang South Sulawesi tungro virus inoculum including morphological characteristics. This study was conducted at the Tungro Disease Research station from June to September 2020. A total of 14 lines were tested for resistance compared to the Tukad Petanu, Tukad Balian, Inpari 8 and Tukad Unda lines against the tungro disease. The rice lines were planted in the form of an augmented design consisting of five blocks. Each block contained three test lines and four comparison varieties, the lines were planted in plots (1 × 5) m, with 25 × 25 cm spacings. The results showed that the population of green leafhoppers at the age of 20 DAP and 30 DAP was found to range from 1 to 95 individuals per line/variety, while the incidence of tungro disease was 1.3 to 11.3% in the three test lines, namely STLRG17 15 LR 1, STLRG17 15 LR 2, and STLRG17 108 LR 1. The highest 1000 seed weight was found in the STLRG17 176 LR 2 line (25.1 g) and the lowest was STLRG17 51 LR 1 (17.6 g). The STLRG17 175 LR 1, STLRG17 176 LR, STLRG17 -175-LR-1, STLRG17-28-LR-1, and STLRG17-26-LR-2 5 lines had a fairly good and consistent appearance at 1000 seed weight, higher yield, productive tillers, plant height, and resistance to tungro disease compared to the comparison varieties.